Hospital pharmacy attachment: a structured experiential training for future pharmacists / Nor Elyzatul Akma Hamdan and Dr. Gurmeet Kaur Surindar Singh - Hamdan, Nor Elyzatul Akma; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
From December 5th 2022 to January 11th 2023, a Hospital Pharmacy Attachment (HPA) was conducted at the Pharmacy Department of Hospital Al Sultan Abdullah, Universiti Teknologi MARA (UiTM). HPA was a structured experiential training conducted over a time frame of 10 working days, offered in the final year of the Bachelor of Pharmacy programme. HPA is a compulsory training aimed at providing an overview and introduction to pharmacy units, exposing students to the organisational structure, the pharmacist’s role, its governing guidelines, and standard operating procedures. The attachment involved training at six main pharmacy units: the in-patient, out-patient, drug information centre, hospital pharmacy administration and store management, chemotherapy drug reconstitution, and total parenteral nutrition.